Characteristics Of Leper Disease: Literature Review - Dwi Yupitasari Sunarto; Nurelly Noro Waspodo; Asrini Safitri (Sean Institute, 2024)
According to the World Health Organization (WHO), leprosy is a chronic infectious disease that attacks the skin and peripheral nerves caused by Mycobacterium Leprae. Leprosy or what is known as Morbus Hansen can occur in all age groups, several other factors are thought to contribute to the increase in leprosy cases, one of which is age, gender, type of leprosy, education, employment and socio-economic factors. The aim of this literature is to determine the characteristics of leprosy. The research method used in the results of this research is Literature Review or literature review. Related keywords are